Pengaruh Kreativitas Guru terhadap Minat Belajar Pendidikan Agama Kristen Siswa kelas X SMK Swasta Persiapan Pematang Siantar Tahun Pembelajaran 2024/2025 - Erni Ropidianti Sianturi; Sabar Rudi Sitompul; Limmarten Simatupang; Raikhapoor Raikhapoor; Eduward Hottua Hutabarat (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The purpose of this study was to determine the positive and significant influence of teacher creativity on the interest in learning PAK of class X students of SMK Swasta Persiapan Pematang Siantar in the academic year 2024/2025. The method used in this study is a quantitative method with inferential descriptive statistics. The population was 130 class X students of SMK Swasta Persiapan Pematang Siantar and a sample of 40 people was determined using a random sampling technique. Data were collected using a positive closed questionnaire of 35 items. The results of the data analysis show that there is a positive and significant influence between the Creativity of Christian Religious Education teachers on the Learning Interests of class X students of SMK Swasta Persiapan Pematang Siantar Academic Year 2024/2025, as evidenced by the following data analysis: 1) Analysis requirements test: a) positive influence test obtained rxy value = 0.551> rtable ( = 0.05, n = 40) = 0.312 thus it is known that there is a positive influence between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.072> ttable ( = 0.05, dk = n-2 = 38) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="25.127" + 0.912X. b) Regression determination coefficient test (r2) = 30.4%. 3) Hypothesis testing using the F test obtained Fcount > Ftable, namely 16.581 > 4.08. Thus Ha is accepted and H0 is rejected.